Analisis Hubungan antara Jam Olah dengan Kinerja Pabrik Kelapa Sawit - M Hudori; Rahajeng Mahadibyanti (Politeknik Kelapa Sawit Citra Widya Edukasi, 2020)
The performance of palm oil mill (POM) can be seen from several indicators, such as oil extraction rate (OER), kernel extraction rate (KER), throughput, oil losses and kernel losses. The achievement of these indicators may be related to the processing time of the POM. The purpose of this research was to determine the relationship between the processing time on the performance of POM, especially OER, KER, throughput, oil losses and kernel losses. The method used is correlation analysis, which is a statistical analysis to see the relationship between two variables, ie the processing time variable with each of these performance variables. The result of the analysis show that the processing time have a weak and negative relationship to OER, KER and oil losses, weak and positive to kernel losses, and strong and negative to throughput. The increase in processing time had a bad impact on the four indicators, ie OER, KER, throughput and kernel losses, but had a good impact on oil losses.